Socialization of Multiculturalism: (Strengthening Understanding of the Concept of Multiculturalism in Students of SMPN 1 Botupingge, Bone Bolango Regency) - Roni Lukum; Lucyane Djaafar; Zulaecha Ngiu; Abdul Haris M. Madina; Sintia Rahmayanti Y. Butudoka; Sudarman M. Damiti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Community service activities in the student environment of SMP Negeri 1 Botupingge, Bone Bolango Regency are carried out with the aim of: (1) Increasing nationalism attitudes through community character who carry out the tradition of multiculturalism among students in Bone Bolango Regency. This socialization concern is carried out because in several regions in Indonesia there is often friction between ethnicities, both influenced by religious, racial and cultural issues that affect national resilience. So it is necessary to socialize early to the students to be able to minimize inter-ethnic conflicts in the Bone Bolango area. (2). In addition, the purpose of this socialization is to make students able to think creatively and innovatively in solving problems faced in society if there is friction caused by provocations aimed at clashing between one tribe and another. (3). Make a contributionpositif bagi para siswa tentang pentingnya pemahaman membangun tradisi multiculturalism in maintaining the Unitary State of the Republic of Indonesia. With this awareness, it will have a positive impact on an area in anticipating the disintegration of the nation in the form of conflicts between tribes in the Bone Bolango Regency area of Gorontalo Province.